1, 2-Dichloroethane impairs glucose and lipid homeostasis in the livers of NIH Swiss mice. (1st April 2017) - Wang, Ting; Xu, Dandan; Fan, Qiming; Rong, Weifeng; Zheng, Jiewei; Gao, Chen; Li, Guoliang; Zeng, Ni; Guo, Tao; Zeng, Lihai; Wang, Fei; Xiao, Chen; et al.
Highlights: 1, 2-DCE exposure to mice induced mild hepatoxicity. 1, 2-DCE exposure led to mouse hepatic glycogen, FFA and triglyceride accumulation. 1, 2-DCE administration induced Akt1 phosphorylation level in mouse livers. 1, 2-DCE treatment resulted in decreases in hepatic G6PC and PYGL expression. The hepatic glycogen accumulation is mediated by 2-CA-induced Akt1activation. Abstract: Excessive exposure to 1, 2-Dichloroethane (1, 2-DCE), a chlorinated organic toxicant, can lead to liver dysfunction. To fully explore the mechanism of 1, 2-DCE-induced hepatic abnormalities, 30 male National Institutes of Health (NIH) Swiss mice were exposed to 0, 350, or 700 mg/m 3 of 1, 2-DCE, via inhalation, 6 h/day for 28 days. Increased liver/body weight ratios, as well as serum AST and serum ALT activity were observed in the 350 and 700 mg/m 3 1, 2-DCE exposure group mice, compared with the control group mice. In addition, decreased body weights were observed in mice exposed to 700 mg/m 3 1, 2-DCE, compared with control mice. Exposure to 350 and 700 mg/m 3 1, 2-DCE also led to significant accumulation of hepatic glycogen, free fatty acids (FFA) and triglycerides, elevation of blood triglyceride and FFA levels, and decreases in blood glucose levels. Results from microarray analysis indicated that the decreases in glucose-6-phosphatase catalytic subunit (G6PC) and liver glycogen phosphorylase (PYGL) expression, mediated by the activation of AKT serine/threonine kinase 1 (Akt1), might be responsible for the hepatic glycogen accumulation and steatosis. Further in vitro study demonstrated that 2-chloroacetic acid (1, 2-DCE metabolite), rather than 1, 2-DCE, up-regulated Akt1 phosphorylation and suppressed G6PC and PYGL expression, resulting in hepatocellular glycogen accumulation. These results suggest that hepatic glucose and lipid homeostasis are impaired by 1, 2-DCE exposure via down-regulation of PYGL and G6PC expression, which may be primarily mediated by the 2-chloroacetic acid-activated Akt1 pathway.